2001
DOI: 10.2307/4003579
|View full text |Cite
|
Sign up to set email alerts
|

Principles and Practices for Managing Rangeland Invasive Plants

Abstract: Invasive plants reduce the capacity of ecosystems to provide goods and services required by society, alter ecological processes, and can displace desirable species. They can reduce wildlife habitat quality, riparian area integrity, rangeland economic value, and enterprise net returns. The invasion process is regulated by characteristics of the invading plant and the community being invaded. The presence and spread of invasive plants is often symptomatic of underlying management problems that must be corrected … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
29
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 119 publications
(29 citation statements)
references
References 101 publications
0
29
0
Order By: Relevance
“…Bison are famous for their tendency to regularly move over large distances (Berger and Cunningham 1994) and their wallows are therefore widely dispersed and numerous across most of Santa Catalina Island (Figure 1). Bison wallowing creates multiple small-scale disturbances at the soil surface that provide safe sites for seedling establishment (Bossard 1991;Hobbs and Huenneke 1992;Masters and Sheley 2001), ultimately resulting in higher overall germination (Stromberg and Griffin 1996). Importantly, nonnative annual grasses tend to allocate fewer resources to roots and more resources to leaf and seed production than perennial grasses, which allow them to grow more quickly and exploit disturbances better (Stromberg and Griffin 1996;Kotanen 1997;Seabloom et al 2003).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…Bison are famous for their tendency to regularly move over large distances (Berger and Cunningham 1994) and their wallows are therefore widely dispersed and numerous across most of Santa Catalina Island (Figure 1). Bison wallowing creates multiple small-scale disturbances at the soil surface that provide safe sites for seedling establishment (Bossard 1991;Hobbs and Huenneke 1992;Masters and Sheley 2001), ultimately resulting in higher overall germination (Stromberg and Griffin 1996). Importantly, nonnative annual grasses tend to allocate fewer resources to roots and more resources to leaf and seed production than perennial grasses, which allow them to grow more quickly and exploit disturbances better (Stromberg and Griffin 1996;Kotanen 1997;Seabloom et al 2003).…”
Section: Discussionmentioning
confidence: 97%
“…One correlate of invasion success is the number of seeds dispersed into new areas; the probability that at least some propagules will reach a safe site and successfully germinate increases with seed availability (Williamson 1996;Masters and Sheley 2001; but see Seabloom et al 2003). Moreover, long-distance dispersal events and multiple introduction points can increase the rate of invasion and spatially distribute plant populations, such that extinction of invasive plants at the local level will have reduced impact at a regional scale (Kiviniemi and Eriksson 1999;Fagan et al 2002;National Research Council 2002).…”
Section: Introductionmentioning
confidence: 99%
“…Invasion by exotic grasses is concerning because they often increase fire frequency and negatively impact native vegetation (Torell et al 1961;Hughes et al 1991;D'Antonio and Vitousek 1992;Brooks et al 2004;Milton 2004). Increases in fire frequency are ecosystem-level changes that can further facilitate invasion and perpetuate the dominance of wildlands by exotic grasses (D' Antonio and Vitousek Exotic plant invasions have been reported to decrease biodiversity, reduce productivity, degrade wildlife habitat, displace native plants, and alter ecosystem functions in wildlands (DiTomaso 2000;Mack et al 2000;Simberloff 2005;Masters and Sheley 2001). However, some ecologists argue the impacts of exotic plants have been exaggerated and that biodiversity and other important plant community characteristics are commonly improved with invasion.…”
Section: Introductionmentioning
confidence: 96%
“…Railway development itself is a disturbance of the environment and has the potential for increasing dissemination of propagules, which makes the ecosystems more susceptible to invasion by alien species (Richardson & Van Wilgen 2004). The disturbed area is particularly important during the early stage of invasion because it creates vacant niches that alien plants can colonise (Masters & Sheley 2001). Rutkovska et al (2013) found that some of the alien taxa in Latvia were associated with topsoil disturbance because of the construction and maintenance of railway lines.…”
Section: Limitations Of the Satellite Imagementioning
confidence: 99%